131k views
1 vote
Write the quadratic function f(x) = x2 - 5x + 3 in vertex form.

A) f(x) = (x - 2.5)2 + 3
B) f(x) = (x + 2.5)2 + 3
C) f(x) = (x - 2.5)2 - 3.25
D) f(x) = (x + 2.5)2 - 3.25

User Pethical
by
5.8k points

1 Answer

4 votes

Answer:

C.
f(x) = (x-2.5)^(2)-3.25

Explanation:

The vertex form for a quadratic function is:


f(x) = a(x-h)^2+k

  • Then, you expand the binomial and get:


f(x) = a(x^2-2hx +h^2) + k

  • Now you distribute and get the first form:


f(x) = ax^2-2ahx +ah^2 + k

  • You know that the general form for a quadratic function is:


f(x) = ax^2+bx+c, Second\ form

  • You compare the two forms that you have and finding h and k:


ax^2+2ahx +ah^2 + k = ax^2+bx+c

  • Finding h from the coefficient of X:


-2ah = b


h = -(b)/(2a)

from the quadratic function given you know that a = 1 , b = -5 and c = 3, thus:


h = -((-5))/(2(1))=2.5

  • Finding k from the third coefficient:


ah^2+k = c


Isolate\ k =>\ k = c-ah^2

You know c,a and h, so replace the values:


k = 3-(1)(2.5)^2 \\ k = 3-6.25\\ k = -3.25\\

• Finally replace the values for a, h and k in the vertex form:


f(x) = a(x-h)^2+k\\ f(x) = (1)(x-2.5)^2+(-3.25)\\ f(x) = (x-2.5)^2-3.25

So answer is C.
f(x) = (x-2.5)^2-3.25

User Mandarin
by
6.1k points